Thyrotoxic phase of autoimmune Hashimoto's thyroiditis as a manifestation of systemic action of viral hepatitis B (clinical case) - Cherkavskyi, Yevhen; Chepilko, Katerina (The Ukrainian Scientific Medical Youth Journal, 2025)
the described clinical case demonstrates the high diversity of systemic manifestations of acute viral hepatitis B, the difficulty of their diagnosis and treatment. HBV has a high prevalence and a significant burden on the medical system of Ukraine. Knowledge and understanding of the clinical manifestations of this nosology requires the attention of doctors of any specialty: from family doctors to endocrinologists. The formation of a multidisciplinary approach and the creation of unified centers for the diagnosis and treatment of viral hepatitis are necessary to reduce the annually increasing morbidity and mortality of the population not only in Ukraine, but also throughout the world.